Leptospirosis enYucatán. De Hideyo Noguchi hasta la actualidad. - Cárdenas-Marrufo, María Fidelia; del Rosario Pech-Sosa, Nayely (Revista Biomedica)
Leptospirosis is a zoonotic disease caused by the pathogenic spirochetes, Leptospira. The disease has a significant impact in several regions of the world; the WHO classifies it as an emerging public health problem due to the epidemic potential that it can have; mainly, because it is related to hydrometeorological conditions. Symptoms include sudden fever, severe headaches, muscle pain, nausea, and chills. Leptospirosis is considered a neglected disease that is associated with populations living in vulnerable conditions in urban and rural environments. Many cases of leptospirosis are related to specific occupations, such as agriculture and animal management. The impact on animal health is reflected in economic losses and risk situations intertwine the humananimal-ecosystem triad. Leptospirosis has been present since ancient times and even today, it is observed that its incidence remains in force. The lack of clinical suspicion its non-specific symptoms, and the limited availability of timely diagnosis among physicians, make it an unknown disease. In this paper, a systematic review of the literature from PubMed, Scielo, Latindex and Google Scholar is presented, and it describes the historical view of the epidemiology of leptospirosis in Yucatan.